2012
DOI: 10.2460/ajvr.73.7.952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine and dobutamine on isoflurane-induced hypotension in Hispaniolan Amazon parrots (Amazona ventralis)

Abstract: Dobutamine CRI at 5, 10, and 15 μg/kg/min and dopamine CRI at 5, 7, and 10 μg/kg/min may be useful in correcting severe hypotension in Hispaniolan Amazon parrots caused by anesthesia maintained with 2.5% isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Isoflurane is known to be a vasodilator (Schnellbacher et al. ) and the consequent decrease in systemic vascular resistance may represent the main cause of hypotension; the degree of hypotension has been correlated with depth of isoflurane anaesthesia in other avian species (Ludders et al. ; Naganobu & Hagio ; Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane is known to be a vasodilator (Schnellbacher et al. ) and the consequent decrease in systemic vascular resistance may represent the main cause of hypotension; the degree of hypotension has been correlated with depth of isoflurane anaesthesia in other avian species (Ludders et al. ; Naganobu & Hagio ; Kim et al.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, no differences were reported in arterial blood pressure during ISO or SEVO anaesthesia in bald eagles (Joyner and others 2008) and red‐tailed hawks (Granone and others 2012). Hypotension can be explained by a decrease of the systemic vascular resistance following the vasodilator effect of these inhalant agents (Souza and others 2005, Schnellbacher and others 2012). Hypotension can also be observed in association with cardiac arrhythmias (Lichtenberger 2005).…”
Section: Discussionmentioning
confidence: 99%